PHILANTHROPY AMONG EMERGING MIDDLE-CLASS MUSLIMS IN THE INTEGRATED ISLAMIC SCHOOLS NETWORK (JSIT): NEGOTIATING RELIGIOUS COMMODIFICATION AND SOCIAL PIETY - Ningrum, Ririn Tri Puspita; Siswanto, Siswanto; Djalaluddin, Ahmad; Huda, Muhammad Muchlish (UIN Antasari Banjarmasin, 2025)
This article examines the reciprocal relationship between the commodification of religion and philanthropic practices at integrated Islamic primary schools within the Integrated Islamic Schools Network (JSIT) in Ponorogo, East Java. Using an ethnographic case study, the research focuses on middle-class Muslim families to understand how religious and philanthropic activities are transformed into commodities. Data were collected through interviews, observations, and documentation involving middle-class Muslims and educators from the tarbiyah community, affiliated with the Prosperous Justice Party (PKS). The study reveals that the rise of the Muslim middle class in Ponorogo, reflecting broader national trends, is shaped by political, cultural, and ideological dynamics. A key finding is the transformation of parental philanthropy into a form of “social piety,” where giving is reframed as both religious devotion and social responsibility. Schools and educators actively cultivate this practice by repackaging Islamic values into attractive commodities that align with middle-class aspirations. The study contributes by showing how philanthropy functions not only as an economic resource but also as a cultural and political instrument in shaping Muslim middle-class identity. It advances debates on the commodification of religion and highlights the socio-political role of philanthropy in contemporary Indonesian Islam.